Antecedentes Morfológicos Y Genecologicos de Maytenus boaria - Donoso, Claudio; Wendler, Jorge (Bosque (Valdivia), 1985)
Considering the possible utilization of Maytenus boaria Mol. and the variety of forms observed, a study was initiated to verify the causes of phenotypic variation of the tree. Samples of leaves, flowers, fruits and seeds were collected from 22 sites located between parallels 33°20’ and 41°08’ South and from 80 to 700 m.a.s.l.; six trees were sampled from each site. A morphological analysis of the characters was performed; germination was tested to analyse the response of the provenances to different periods of stratification. It was found that a clinal variation exists in the characteristic lenght/width ratio of the leaves; leaves become longer and narrower towards the south ; there is a clinal variation in the germination capacity of the seeds in response to diferent periods of stratification in wet sand at about 4°C; this response to stratification is significant in the North (Central Valley) and decreases clinally towards the south along the Central Valley and also towards the higher elevations in the Andes. A high degree of variability characterized the reproductive structure such as flowers and fruits. This variability was not correlated with latitude, altitude or specific habitats; this fact suggests that the origin of the polymofism of the species is plasticity rather than genecological differentiation. In addition it was shown that Maytenus boaria is dioecius, that there are two forms or varieties which dp not constitute separate populations, and that the range of distribution extends of the southern limit of continental Aysén (Parallel 49°S. Lat.)